Rain Forest: A Close-UpLlook at the Natural World of a Rain Forest - Greenaway, Frank; Taylor, Barbara 1954- (New York : Dorling Kindersley, 1992)
Examines the variety of life found in a rain forest, including the flying gecko, poison dart frog, and curly-haired tarantula.
Includes index.
Keywords: Rain forest animals -- Juvenile literature; Rain forest plants -- Juvenile literature